Mucocele of the appendix presenting as an exacerbated chronic tubo-ovarian abscess: A case report and comprehensive review of the literature. Issue 39 (September 2019) - Cubro, Hajrunisa; Cengic, Vesna; Burina, Nina; Kravic, Zlatko; Beciragic, Esad; Vranic, Semir
Abstract: Rationale: Appendiceal mucocele is a rare entity of mucinous cystic dilatation of the appendix. It has no typical clinical presentation and is considered a potentially premalignant condition. Patient concerns: We present a case of accidental intraoperative finding of an appendiceal mucocele in a 54-year old woman that clinically presented with an exacerbated chronic tubo-ovarian abscess. Diagnoses: Trans-vaginal ultrasonography showed an encapsulated, oval, unilocular mass above the uterus with a heteroechogenic structure, homogeneous fluid content, and smooth regular walls without inner proliferation. The histopathologic diagnosis was consistent with an appendiceal cystadenoma. Interventions: The patient underwent a simple appendectomy. Outcomes: There were no clinical, biochemical or imaging signs of the disease recurrence at 6 months follow up. Lessons: To our knowledge, this is the only well-documented case of appendiceal mucocele mimicking exacerbated chronic tubo-ovarian abscess reported in the literature. Awareness of a rare entity such as an appendiceal mucocele, which is frequently misdiagnosed as a potential cause of acute abdomen, is necessary for the appropriate management strategy in order to prevent complications.